Acute‐phase response following full‐mouth versus quadrant non‐surgical periodontal treatment: A randomized clinical trial2. (1st October 2015) - Graziani, Filippo; Cei, Silvia; Orlandi, Marco; Gennai, Stefano; Gabriele, Mario; Filice, Natalia; Nisi, Marco; D'Aiuto, Francesco
Abstract Aim A moderate acute‐phase response occurs 24‐h following full‐mouth non‐surgical treatment (FM‐SRP). The aim of this study was to compare acute‐phase (24‐h) and medium‐term (3 months) inflammation after quadrant scaling (Q‐SRP) versus FM‐SRP. Material & Methods Thirty‐eight periodontitis‐affected subjects were randomly allocated to FM‐SRP or Q‐SRP after a baseline visit. Periodontal and anthropometric parameters were collected at baseline and 3 months. Serum samples were drawn at baseline, 1, 7, and 90 days after treatment. High‐sensitivity assays of inflammation and endothelial assays were performed. Results FM‐SRP produced a greater acute‐phase response after 24 h [threefold increase in C‐reactive protein (CRP), twofold increase in interleukin (IL‐6), and a slight increase in tumour necrosis factor]. No differences in systemic biomarkers were noted between groups at any later follow‐ups. Both periodontal treatments produced a comparable improvement in clinical periodontal parameters with no between‐group differences. Treatment time was positively associated with the relative 24‐h increase in CRP (R = 0.5, p < 0.001) and IL‐6 (R = 0.5, p = 0.002), while the number of deeper (>6 mm) pockets predicted only the relative increase in IL‐6 (R = 0.4, p < 0.05). Conclusions FM‐SRP triggers a moderate acute‐phase response of 24 h duration compared to Q‐SRP. Further research is needed to assess the eventual impact of such findings on the risk of vascular events is advocated. (ClinicalTrials.gov NCT01857804).